Chronic kidney disease and its complete scenario, management of chronic kidney disease by clinical pharmacists - a prospective interventional study - D, Padma Priya; K, Jagadeeshwari; N, Prema Kumari; M, Abhisekhar; V, Uma Sankar (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2022)
Chronic kidney disease is a growing epidemic worldwide. Nearly two-thirds of CKD patients have diabetes mellitus, hypertension, and both comorbid conditions. Several disease management programs are developed and they implement with help of physicians, and highly trained clinical pharmacists to improve disease management and improve clinical outcomes. The goals of clinical pharmacist in the management of CKD patients by focusing on Four key areas: To obtain information about medication non-adherence, To assess the patient complications for dialysis, to assess the prevalence of chronic kidney disease patients, To evaluate the clinical pharmacist’s role in improving patient medication adherence, To identify the correlation between CKD and other comorbidities, To observe the drug interactions in prescribed drugs. Lack of patient knowledge on CKD disease conditions, and limited reimbursement, lack of primary care by physicians and health care professionals are all barriers that must be overcome with help of the clinical pharmacist role in the management of CKD.